2016
DOI: 10.1371/journal.pone.0148041
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Drug-Resistant Tuberculosis in Mainland China: An Updated Systematic Review and Meta-Analysis

Abstract: BackgroundIn recent years, drug resistant tuberculosis (DR-TB) particularly the emergence of multi-drug-resistant tuberculosis (MDR-TB) has become a major public health issue. The most recent study regarding the prevalence of drug-resistant tuberculosis in mainland China was a meta-analysis published in 2011, and the subjects from the included studies were mostly enrolled before 2008, thus making it now obsolete. Current data on the national prevalence of DR-TB is needed. This review aims to provide a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 8 publications
6
34
2
Order By: Relevance
“…Sharma et al reported a higher proportion of drug resistance in defaulters among previously treated patients in Delhi [24]. Similar results to our study were reported by Baya et al (OR = 3.82, 95% CI (1.87-7.79), p = 0.0002) [20]. This may be because in failure cases, the bacteria have a higher chance of developing resistance due to prolonged exposure to the drugs and also the bacteria are expected to be more resilient to the drugs which led to a failure of treatment in the first place.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sharma et al reported a higher proportion of drug resistance in defaulters among previously treated patients in Delhi [24]. Similar results to our study were reported by Baya et al (OR = 3.82, 95% CI (1.87-7.79), p = 0.0002) [20]. This may be because in failure cases, the bacteria have a higher chance of developing resistance due to prolonged exposure to the drugs and also the bacteria are expected to be more resilient to the drugs which led to a failure of treatment in the first place.…”
Section: Discussionsupporting
confidence: 91%
“…As per some Indian studies, the prevalence of any drug resistance among previously treated TB patients was 37%-62.77% [6,[16][17]. As per a few international studies, the prevalence of any drug resistance among previously treated TB patients was between 7.7%-81.7% [18][19][20].…”
Section: Discussionmentioning
confidence: 94%
“…In the end, we found out older age, previous treatment history and poor compliance as independent susceptibility factors for MDR/RR-TB, which were consistent with other studies (Duan et al, 2016;Li et al, 2016;Lv, Lu, Shi, & Zhou, 2017). More importantly, we reported, for the first time that allele HLA-DRB1*08:01 was an independent risk factor for MDR/RR-TB, especially for primary transmitted MDR/RR-TB in the Han population from Hubei province, China, which warrants further studies with larger sample size.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of MDR-TB cases in the present study was 5% in Prefecture E and 10% in Prefecture W, which was lower than the proportion of incident MDR-TB cases in China (12%) based on a previous meta-analysis [19]. Meanwhile, a substantial spatial difference in the MDR-TB burden between Prefecture E and Prefecture W was observed in the current study, which was consistent with recent systematic reviews [19,20]. The difference in the prevalence of culture-positive TB and MDR-TB amongst diagnosed TB patients between the eastern and western sites might be due to social economic status, educational level, population density and mobility, proportion of ethnic minorities, and distribution of relevant diseases based on geographic features.…”
Section: Discussionsupporting
confidence: 89%